Analisis Permasalahan Penerapan ISAK 16 dalam Pengakuan Aset Konsesi pada Perusahaan Jasa Kepelabuhan dan Pengerukan (Studi Kasus pada Audit KAP XYZ) - Dandi Aprila; Ali Tafriji Biswan; Ni Komang Maysarah Darapalgia (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This study is motivated by the limited number of studies examining the application of ISAK 16 in the recognition of concession assets in the port services and dredging sector, despite the fact that this issue affects the reliability of financial statements and audit credibility. The objective of this study is to analyze the practices of applying ISAK 16, identify the emerging problems, and assess the conformity of these practices with asset control theory and accounting compliance theory. This research employs a qualitative approach using a case study design conducted at a port services company audited by KAP XYZ. The research participants consist of seven informants selected through purposive sampling, including management, accounting staff, and auditors. Data were collected through semi-structured interviews and a review of audit documentation, and subsequently analyzed using thematic analysis to identify patterns and the root causes of issues in the implementation of the standard. The results indicate that the company continues to recognize concession assets as property, plant, and equipment due to considerations related to financial ratio stability and limited understanding of ISAK 16. Audit recommendations have not been fully implemented due to the absence of explicit internal policies governing the accounting treatment of concession assets. These findings reinforce asset control theory, which emphasizes that asset recognition should be based on control over economic benefits rather than legal ownership, and support accounting compliance theory, which highlights the influence of organizational factors on standard implementation. This study concludes that non-compliance with ISAK 16 arises not only from technical aspects but also from behavioral and institutional factors. The findings imply the need for enhanced professional accounting capacity and updated accounting policies to strengthen compliance with accounting standards.